An overview of flood mitigation strategy and research support in South Asia: implications for sustainable flood risk management. Issue 1 (2nd January 2016) - Abbas, Azhar; Amjath-Babu, T.S.; Kächele, Harald; Usman, Muhammad; Müller, Klaus
Abstract : South Asia faces increasing flooding risks due to climatic and socio-economic changes. Various measures have been adopted by the governments of the countries in this region. However, these measures are not adequate to protect the vulnerable communities from ever-increasing flood losses. This study assesses the policy and planning processes and flood-related scientific research in India, Pakistan and Bangladesh. Based on a systematic review, a comparison of the existing flood management systems of the three countries is undertaken, and a framework for sustainable flood management in the region is suggested. Insights from the literature show that Bangladesh has been able to develop an effective governance structure to address flood hazards, while Pakistan's approach to flood management planning is found to be largely inadequate. This inadequacy is mainly attributed to missing links in policy formulation and planning processes, along with a lack of institutional coordination. The results of the literature analysis reveal poor support from scientific research focusing on flooding issues in the case of Pakistan, while Bangladesh and India seem to have benefited from research support in formulating their flood management strategies. Based on these findings, an alternative framework is suggested, emphasizing the need to enhance institutional linkages, community participation and evidence-based research.